Performances of the RC column under close-in explosion induced by the double-end-initiation explosive cylinder. (October 2019) - Chen, Li; Hu, Ye; Ren, Huiqi; Xiang, Hengbo; Zhai, Chaochen; Fang, Qin
Highlights: Field tests reveal a compression-shear failure of RC column subjected to double-end-initiated explosive. The axial load loads exert a significant influence on the failure characteristics of the RC column. Charge shape and detonation method affect the failure characteristics of RC column under close-in explosion. A damage coefficient equation was proposed with consideration to size of charge and axial load ratio. Abstract: The axial load-carrying column is commonly considered as the most critical component in RC structure. To determine the failure characteristics of the RC column under the combined action of axial load and close-in explosion initiated at two ends of an explosive cylinder, large-scale blast tests were carried out, with consideration to different charge mass and axial load ratio (ALR). A new compression-shear failure mode was first reported and discussed. The post-blast RC columns were then transported to the laboratory to measure the residual axial-bearing capacity with a hydraulic testing machine. A high-fidelity finite element (FE) model was developed in LS-DYNA, and intense simulations reveal the different failure characteristics of the RC column subjected to different point-initiation. A damage assessment on the post-blast RC column was conducted based on the residual axial-bearing data. Parametric study was carried out to find out the influences of ALR, scaled distance, diameter to length (D/L) ratio of charge, column aspect ratio, longitudinal reinforcement ratio, and transverse reinforcement ratio on the failure characteristics and residual axial-bearing capacity. Finally, an empirical equation was proposed on the multivariate analysis, which provides an effective method to rapidly assess the damage degree of the RC column subjected to double-end-initiation, simultaneously considering the charge shape and the axial load ratio.